2019
DOI: 10.17505/jpor.2019.11
|View full text |Cite
|
Sign up to set email alerts
|

Are Processes in Acceptance & Commitment Therapy (ACT) Related to Chronic Pain Outcomes within Individuals over Time? An Exploratory Study Using n-of-1 Designs

Abstract: (2019). Are processes in Acceptance & Commitment Therapy (ACT) related to chronic pain outcomes within individuals over time? An exploratory study using n-of-1 designs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…A case report is purely descriptive, whereas a single-case study demonstrates rigorous methods for the study design and data analysis using visual and statistical methods whenever possible (17). A single-case study design is a common study design in health care (17)(18)(19), e.g., in psychiatric disorders, such as schizophrenia (13,20,21). This design addresses intraindividual differences (16,17,22) and contributes to individualized medicine (12,23).…”
Section: Introductionmentioning
confidence: 99%
“…A case report is purely descriptive, whereas a single-case study demonstrates rigorous methods for the study design and data analysis using visual and statistical methods whenever possible (17). A single-case study design is a common study design in health care (17)(18)(19), e.g., in psychiatric disorders, such as schizophrenia (13,20,21). This design addresses intraindividual differences (16,17,22) and contributes to individualized medicine (12,23).…”
Section: Introductionmentioning
confidence: 99%
“…In the sixth and final article, Trompetter, Johnston, Johnston, Vollenbroek-Hutten and Scheurs ( 2019 ) describe an exploratory study where they used a single-case design to study processes in three patients treated for chronic pain by Acceptance and Commitment Therapy (ACT). Although they found no treatment effects of the ACT intervention in these three patients, the results showed that in two of the patients pain interference co-varied with both experiential avoidance and values-based living, in a direction that is predicted from ACT theory.…”
mentioning
confidence: 99%